2019
DOI: 10.3390/socsci8060164
|View full text |Cite
|
Sign up to set email alerts
|

‘You Scratch My Back and I’ll Scratch Yours’? Support to Academics Who Are Carers in Higher Education

Abstract: In recent years, it has become common for individuals to juggle employment and unpaid care work. This is just as true for the England-based academic workforce, our focus in this article. We discuss how, in the context of English Higher Education, support for carers is enacted and negotiated through policies and practices of care. Our focus on academics with a diverse range of caring responsibilities is unusual insofar as the literature on care in academia is overwhelmingly concerned with parents, usually mothe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…It suggests that this male leader at least does not have significant caring responsibilities and is able to take part in hobbies and other activities that provide a distraction from the school workplace and help him to unwind. This is consistent with the work of Moreau and Robertson (2019) who found considerable differences in in the caring responsibilities of male and female education leaders across the education workforce. They identified that many white, middle-class, male heterosexual educators had a ‘bachelor boy’ (p.5) existence and were less likely to experience the tensions arising from combining care and paid work.…”
Section: Discussionsupporting
confidence: 90%
“…It suggests that this male leader at least does not have significant caring responsibilities and is able to take part in hobbies and other activities that provide a distraction from the school workplace and help him to unwind. This is consistent with the work of Moreau and Robertson (2019) who found considerable differences in in the caring responsibilities of male and female education leaders across the education workforce. They identified that many white, middle-class, male heterosexual educators had a ‘bachelor boy’ (p.5) existence and were less likely to experience the tensions arising from combining care and paid work.…”
Section: Discussionsupporting
confidence: 90%
“…Academic mothers are subject to career delays due to pregnancy, childbirth and nursing, and many university campuses are ill-equipped to accommodate the physical aspects of motherhood (Trussell, 2015;McCutcheon and Morrison, 2018;Mirick and Wladkowski, 2018). This is perhaps a larger reflection of how academia views motherhood (Mirick and Wladkowski, 2018;Moreau and Robertson, 2019), which factored into the decision by some academic women to remain single and childless throughout their career (Mason et al, 2013). Women faculty are more likely to be partnered with someone working full-time (Bascom-Slack, 2011) while male faculty are less likely to share the burden of unpaid household and childrearing work with their partners.…”
Section: Impact Of Having Children On Academic Careersmentioning
confidence: 99%
“…A number of the studies analyzed in the literature review focused on specific academic ranks: students (Moreau and Kerner, 2015), doctoral students (Springer et al, 2009;Mirick and Wladkowski, 2018;Wladkowski and Mirick, 2019), the tenure-track years (Comer and Stites-Doe, 2006;Poronsky et al, 2012;Trussell, 2015), or mid-career academics (senior lecturers and associate professors as studied by Harris et al, 2019). Other studies (Rafnsdóttir and Heijstra, 2013;McCutcheon and Morrison, 2018;Huppatz et al, 2019;Moreau and Robertson, 2019;van Engen et al, 2019) included academics from different ranks, but did not consider this variable in the data analysis.…”
Section: Influence Of Academic Rankmentioning
confidence: 99%